2022
DOI: 10.1093/hr/uhac267
|View full text |Cite
|
Sign up to set email alerts
|

Theanine, a tea-plant-specific non-proteinogenic amino acid, is involved in the regulation of lateral root development in response to nitrogen status

Abstract: Glutamine synthetase type I (GSI)-like proteins are proposed to mediate nitrogen signaling and developmental fate by synthesizing yet unidentified metabolite. Theanine, the most abundant non-proteinogenic amino acid in tea plants, is the first identified metabolite synthesized by GSI-like protein (CsTSI) in living system. However, the roles of theanine in nitrogen signaling and development are rarely understood. In the study, we found nitrogen deficiency significantly reduced theanine accumulation and increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…In tea plant roots, both theanine biosynthesis and root development are regulated by N level and its form (Yang et al, 2020). Moreover, theanine is probably involved in N-regulated lateral root development (Chen et al, 2022). This implicates the presence of TFs that can co-regulate theanine biosynthesis and development in the tea root.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In tea plant roots, both theanine biosynthesis and root development are regulated by N level and its form (Yang et al, 2020). Moreover, theanine is probably involved in N-regulated lateral root development (Chen et al, 2022). This implicates the presence of TFs that can co-regulate theanine biosynthesis and development in the tea root.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, CsLBD37 is expressed in pericycle cells and also inhibits lateral root development. It is reported that apoplastic theanine can negatively regulate lateral root development, under high nitrogen levels (Chen et al, 2022). Therefore, CsLBD37 may also be involved in theanine-regulated lateral root development.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have indicated that the accumulation of theanine is subject to dynamic regulation influenced by various factors, such as the growth of tea plants and environmental factors, including development, season, temperature, light, and other abiotic and biotic stresses [ 33–35 ]. Tea plants accumulate theanine dynamically as a result of biosynthesis, degradation, and transport processes, all of which are coregulated by genetics, nitrogen status, and the environment [ 1 , 6 , 36 ].…”
Section: Discussionmentioning
confidence: 99%